The addition of stripes (a version of the 'horizontal-vertical illusion') increases foot clearance when crossing low-height obstacles. Issue 7 (2nd July 2016) - Foster, Richard J.; Buckley, John G.; Whitaker, David; Elliott, David B.
Abstract: Trips over obstacles are one of the main causes of falling in older adults, with vision playing an important role in successful obstacle negotiation. We determined whether a horizontal-vertical illusion, superimposed onto low-height obstacles to create a perceived increase in obstacle height, increased foot clearances during obstacle negotiation thus reducing the likelihood of tripping. Eleven adults (mean ± 1 SD: age 27.3 ± 5.1 years) negotiated obstacles of varying heights (3, 5, 7 cm) with four different appearance conditions; two were obstacles with a horizontal-vertical illusion (vertical stripes of different thickness) superimposed on the front, one was a plain obstacle and the fourth a plain obstacle with a horizontal black line painted on the top edge. Foot clearance parameters were compared across conditions. Both illusions led to a significant increase in foot clearance when crossing the obstacle, compared to the plain condition, irrespective of obstacle height. Superimposing a horizontal-vertical illusion onto low-height obstacles can increase foot clearance, and its use on the floor section of a double-glazing door frame for example may reduce the incidence of tripping in the home. Practitioner Summary: Low-height obstacles such as the floor section of a double-glazing door frame are potential tripping hazards. In a gait lab-based study we found that a horizontal-vertical illusion superimposed onto low-height obstacles led to significantly higher foot clearances; indicating their potential as a useful safety measure.